Where the wild things are - Jonze, Spike; Hanks, Tom.; Goetzman, Gary, 1952-; Sendak, Maurice; Carls, John.; Landay, Vincent; Eggers, Dave.; Keener, Catherine; Records, Max, 1997-; Ruffalo, Mark.; Ambrose, Lauren, 1978-; Cooper, Chris, 1951-; et al. (Burbank, CA : Distributed by Warner Home Video, 2010)
Max has an active imagination, who will throw a fit if others don't go along with what he wants. Following an incident with his sister Claire and her friends, Max throws a tantrum when his mother pays more attention to her boyfriend than to him - runs away from home. Wearing his wolf costume at the time, Max not only runs away physically, but runs toward a world in his imagination. This world, an ocean away, is inhabited by large wild beasts, including Carol who has the same temperament as Max. Instead of eating Max like they normally would with creatures of his type, the wild things befriend Max after he proclaims himself a king who can magically solve all their problems.
Based on the book by Maurice Sendak.
Originally released as a motion picture in 2009.
Special features: Series of "Where the wild things are" shorts by Lance Bange: "The absurd difficulty of filming a dog running and barking at the same time," "Crew pranks Spike," "Vampire attack: the Max Records short" and "The kids take over the picture."
Music, Karen O, Carter Burwell ; cinematography, Lance Acord ; editor, James Haygood, Eric Zumbrunnen.
Catherine Keener, Max Records, Mark Ruffalo, Lauren Ambrose, Chris Cooper, James Gandolfini, Catherine O'Hara, Forest Whitaker.
MPAA rating: PG; for mild thematic elements, some adventure action and brief language.
Keywords: Sendak, Maurice -- Film and video adaptations; Imagination in children -- Drama; Temper tantrums -- Drama; Brothers and sisters -- Drama; Mothers and sons -- Drama; Children's costumes -- Drama; Runaway children -- Drama; Fantasy films; Film adaptations; Feature films; Video recordings for the hearing impaired